1948
DOI: 10.2307/1538158
|View full text |Cite
|
Sign up to set email alerts
|

The Utilization of Sugars and Other Substances by Drosophila

Abstract: Studies have been made of the use of carbohydrates and other food material by several insects, e.g. the honey-bee (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
32
0

Year Published

1953
1953
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(43 citation statements)
references
References 9 publications
11
32
0
Order By: Relevance
“…One of the pioneering studies in this field was performed by Hassett (27). In general, our conditions closely resembled that report.…”
Section: Discussionsupporting
confidence: 88%
“…One of the pioneering studies in this field was performed by Hassett (27). In general, our conditions closely resembled that report.…”
Section: Discussionsupporting
confidence: 88%
“…Consistent with previous results, we found that sucrose, fructose, maltose, D-glucose, mannose, and sorbitol all robustly supported survival, indicating that they provide metabolically accessible energy to the flies (Fig. 1 A) (Hassett, 1948;Hassett et al, 1950;Burke and Waddell, 2011;Fujita and Tanimura, 2011). By contrast, L-fucose, L-glucose, ribose, and arabinose failed to substantially extend lifespan over water controls, suggesting that they have little or no nutritional value.…”
Section: Relationship Between Sugar Palatability and Nutritional Contentsupporting
confidence: 90%
“…We first wished to define the nutritive content and palatability (appetitive taste) of 10 sugars that previous studies in blowflies and Drosophila (Hassett, 1948;Hassett et al, 1950) To measure nutritional content, we housed adult flies in vials containing 1% agar with each individual sugar as their sole food source. Consistent with previous results, we found that sucrose, fructose, maltose, D-glucose, mannose, and sorbitol all robustly supported survival, indicating that they provide metabolically accessible energy to the flies (Fig.…”
Section: Relationship Between Sugar Palatability and Nutritional Contentmentioning
confidence: 99%
“…The involvement of oxidative stress in D-galactose-induced life shortening has not been well studied in fruit flies and houseflies. We should emphasize that the life-shortening effect of Dgalactose is not due to the change of the optimal compositions of the diet because it has been shown that using other mono-or di-saccharides, such as fructose, maltose and sucrose to substitute D-glucose did not cause life-shortening (Hassett 1948). Jordens et al (1999) showed that D-galactose shorten the lifespan of Drosophila and R-deprenyl prevented the lifespan shortening.…”
Section: Discussionmentioning
confidence: 96%